If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -7 = 6x Reorder the terms: -7 + 8x = 6x Solving -7 + 8x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -7 + 8x + -6x = 6x + -6x Combine like terms: 8x + -6x = 2x -7 + 2x = 6x + -6x Combine like terms: 6x + -6x = 0 -7 + 2x = 0 Add '7' to each side of the equation. -7 + 7 + 2x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 2x = 0 + 7 2x = 0 + 7 Combine like terms: 0 + 7 = 7 2x = 7 Divide each side by '2'. x = 3.5 Simplifying x = 3.5
| -26=-5+7(x+8) | | -x+5=11 | | [x]+-8=5 | | x+3+9x-43= | | 50-2x=40 | | 3x+-22=-49 | | 3r-9t+2r+3t= | | 7-.25n=15 | | log(4-x)=0.5 | | 7-.25x=15 | | 0.4(x+40)+1.2x=80 | | 3(-4x+2)=-26 | | -2x+4(x+11)=20 | | -3[2x+6]=12 | | 2(5x-3)=16 | | A=r(2L) | | 5-(4x+53)=-4x | | 9+7n-2=8n+14-2n | | 3x(5x-7)=0 | | R=E(I) | | 3x-5=2-6x | | r=(50+10)(24-2) | | 2x^2+6x+5=10 | | [2x+6]+-4=-20 | | 1+logx=0 | | r=(50+5)(24-1) | | 6+30x=20x+14 | | 87.60=45x+0.20 | | X^2+4x+12=6.48074069841 | | 5x+35=8x-4 | | 2y^2-x^2=11 | | 9y^2-y=0 |